The Irish Catholic clergy, Stuart sovereignty and the 1650 appeal to the Duke of Lorraine - David FINNEGAN (E-REA, 2014)
This article seeks to explore the wide range of Irish Catholic political thinking in the early modern period by looking at its role in shaping events at a moment of particular stress during the British and Irish wars of the mid-seventeenth century. The article focuses on the “Lorraine interlude” when most of Ireland’s Catholic leadership, guided by the clerical hierarchy, were willing to suspend Stuart sovereignty to ensure they received assistance from the Duke of Lorraine in the war against the parliamentarians. This episode revealed that the Irish Catholic attachment to the Stuarts was far from unquestioning. The ‘hidden transcript’ of Irish Catholic political thinking, shaped by the Irish Catholic clergy, intruded into the public sphere and revealed perceptions of faith, nation and state that historians have largely ignored because they do not fit the pre-existing historiographical model of what constituted Irish political thinking in the early modern period.